Mapping the Use of Classification Scheme in South Sulawesi University Libraries in 2023 - Pattah, Sitti Husaebah; Almah, Hildawati; Taufiq, Raihan (Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Classifying library materials is vital for efficient storage, retrieval, and user access to necessary resources. This study aims to map the use of classification schemes in South Sulawesi University libraries and the reasons for choosing to use classification schemes in grouping their collections. This study uses a descriptive qualitative approach by interviewing 49 university librarians in South Sulawesi. The results of the study show that DDC is the most widely used classification scheme by libraries in grouping library materials. The research results indicate that DDC is the most widely used classification scheme by libraries for grouping library materials, with 44 higher education libraries in Sulawesi. The breakdown shows that e-DDC has the highest usage at 57%, followed by the original English DDC at 23%, and the least used is the Indonesian translated compact DDC published by the National Library of the Republic of Indonesia at 10%. Two out of 49 libraries use the LCC and UDC classification schemes. There are still three libraries that need to use the classification scheme but use color codes, KDT, and classification textbooks. The reason for choosing the use of a classification scheme is that the notation is detailed, standardized, and easy to use (original DDC). Another reason is that it is easy to use because it is Indonesian, user-friendly, fast, and efficient, with a search menu and automated system (e-DDC). Furthermore, the reason for the need for more use of the original DDC is that this scheme is English and expensive.